Implementation of Legal Protection for Citizenship Rights of Indonesian Former Transnational Terrorism Actors within he Indonesian Legal System - Lalu Guna Nugraha; Supanto Supanto; Erna Dyah Kusumawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze the implementation of legal protection for citizenship rights of former transnational terrorist Indonesian citizens within Indonesia's legal system. Using normative juridical method with statutory and conceptual approaches, this study examines secondary data from primary, secondary, and tertiary legal materials. The results show that Indonesia's legal system has an adequate legal framework to protect the citizenship rights of former transnational terrorists, although its implementation faces various challenges. The deradicalization program and status verification mechanism implemented by the government have not been fully effective due to inter-institutional coordination constraints and community resistance. Additionally, the study identifies that citizenship status cannot be automatically revoked without proper legal process according to Law No. 12 of 2006 on Citizenship, as terrorist groups cannot be categorized as